Geopolymer Bio-Patch Repair: Microbially-Induced Calcite and Pozzolanic Fly Ash and Rice Husk Ash for Corrosion-Resistant of Reinforced Concrete Repair - Pinta Astuti; Angga Jordi Wisnu Nouvaldi; Aprilia Rahmayanti; Pramudya Surya Shabura; Muhammad Etandra Fara Adzani; Dylan Ataa Tsany; Adhitya Yoga Purnama; Rahmita Sari Rafdinal (Advance Sustainable Science Engineering and Technology, 2026)
Indonesia’s archipelagic environment subjects concrete structures to severe corrosion and sulfate attacks, necessitating sustainable repair solutions. This study evaluates a geopolymer-based bio-patch repair mortar utilizing fly ash (FA), rice husk ash (RHA), and Bacillus subtilis bacteria to induce Microbially Induced Calcite Precipitation (MICP). While the silica-rich ashes act as pozzolanic materials, the bacteria enhance durability by reducing oxygen levels and lowering corrosion rates. Microscopic analysis confirmed the formation of calcium carbonate ($CaCO_3$) and calcium silicate hydrate (C-S-H), both of which significantly improve mechanical properties. The research identified an optimum mixture of 93% FA, 6% RHA, and 1% bacteria, which achieved a compressive strength of 30 MPa, a density of 2.32 g/cm³, and a low water absorption rate of 3.25%. These results meet standard performance requirements, demonstrating that this eco-friendly geopolymer-MICP system is a viable and innovative contribution to structural repair in aggressive environments.